2017
DOI: 10.1002/anie.201708474
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Mechanism of the Monoterpene Cyclolavandulyl Diphosphate Synthase that Catalyzes Consecutive Condensation and Cyclization

Abstract: We report the three-dimensional structure of cyclolavandulyl diphosphate (CLPP) synthase (CLDS), which consecutively catalyzes the condensation of two molecules of dimethylallyl diphosphate (DMAPP) followed by cyclization to form a cyclic monoterpene, CLPP. The structures of apo-CLDS and CLDS in complex with Tris, pyrophosphate, and Mg ion were refined at 2.00 Å resolution and 1.73 Å resolution, respectively. CLDS adopts a typical fold for cis-prenyl synthases and forms a homo-dimeric structure. An in vitro re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 15 publications
1
24
0
Order By: Relevance
“…While this article was undergoing revision, another function/structure paper on a" head-to-middle" prenyltransferase,c yclolavandulyl diphosphate synthase,C LDS,w as reported. [16] Thestructure is very similar to what we find with Mcl22, although the mechanisms of action are different since…”
Section: Angewandte Chemiesupporting
confidence: 85%
“…While this article was undergoing revision, another function/structure paper on a" head-to-middle" prenyltransferase,c yclolavandulyl diphosphate synthase,C LDS,w as reported. [16] Thestructure is very similar to what we find with Mcl22, although the mechanisms of action are different since…”
Section: Angewandte Chemiesupporting
confidence: 85%
“…X‐ray crystallography analyses have revealed that the protein structures of UPP synthase (UPPS), LPPS, CLDS, and Mcl22 adopt a typical fold for the cis ‐type IDS family (Figure ). These structures have allowed mechanistic and structural comparison among the cis ‐type IDS homologous enzymes.…”
Section: Coupling Mechanismmentioning
confidence: 99%
“…The intramolecular proton‐transfer mechanism of the CLDS reaction has been proposed on the basis of the combination of an in vitro reaction in which the regiospecifically 2 H‐substituted DMAPP substrate and the CLDS crystal structure are used (Figures and ) . The CLDS‐catalyzed reaction begins with ionization of the pyrophosphate leaving group of DMAPP with formation of the dimethylallyl cation in the S1 site.…”
Section: Coupling Mechanismmentioning
confidence: 99%
See 2 more Smart Citations